Obstetric and long‐term graft outcomes in pregnant kidney transplant recipients: A single‐center experience. Issue 8 (25th May 2021) - Akcay, Omer Faruk; Yeter, Haci Hasan; Karcaaltincaba, Deniz; Bayram, Merih; Guz, Galip; Erten, Yasemin
Abstract: Background: Kidney transplantation (KT) is the best option for many women with end‐stage renal disease desiring pregnancy. The aim of this study was to investigate obstetric and graft outcomes among KT recipient women in our center. Methods: Maternal and fetal data were assessed in 29 pregnancies of 18 female KT recipients. Each patient was matched with two controls without pregnancy history for factors known to affect graft function. According to pre‐pregnancy levels, serum creatinine and eGFR slope in the gestational and postpartum periods were calculated as percentages. Results: The main maternal and fetal complications were preeclampsia (38%) and preterm births (38%), respectively. Pregnancy (odds ratio [OR]: 5.09; p  = .02), proteinuria in the third trimester (OR: 5.52; p  = .02), proteinuria in postpartum third months (OR: 7.4; p  = .008) and stable creatinine levels in the first 6 months of pregnancy (OR: 11.25 p  = .03) were associated with graft dysfunction. Postpartum first year eGFR decline (−16.8% vs. −6.7%; p  = .04) and second‐year eGFR decline (−18.5% vs. −8.3%; p  = .04) were significantly higher in the pregnancy group than those matched controls. Conclusion: Pregnancy after KT is associated with high rates of maternal and fetal complications. The sustained decline of eGFR may suggest an increased risk of graft loss compared to recipients with similar clinical characteristics.